Dampak Akuntabilitas, Transparansi Dan Pengawasan Terhadap Pengelolaan Dana Desa - Chyntia Ambar Sugiharti; Swarmilah Hariani (Jurnal Riset Manajemen dan Bisnis, 2021)
This study aims to determine the effect of accountability, transparency, and supervision on village fund management. The objects of this study were 10 villages located in Kaloran Subdistrict, Temanggung Regency. This study was conducted on 50 respondents using a quantitative descriptive approach. The results of this study indicate that accountability and transparency have a positive and significant effect on village fund management, while supervision has no significant effect. This study shows that transparency is a crucial factor in fund management, thus, needs to get more attention from stakeholders. The ineffectiveness of supervision shows that the village authorities need to collaborate with government officials and academics to create effective supervisory cooperation.